Spy dog rocket rider - Cope, Andrew, 1966-; De la Rue, James (London : Puffin Books, 2009)
After Lara retires from the secret service, she decides to track down her father, but instead she finds some evil scientists who are trying to build a rocket for a criminal mastermind with plans to cause trouble in space.
3-6.
3-6
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Spies -- Fiction; Dogs -- Fiction; Spy stories; Spy stories